EFEKTIVITAS PELAKSANAAN PENYIDIKAN DI POLRES SAMBAS PASCA DIUNDANGKANNYA PP NOMOR 58 TAHUN 2010 - Prapto Yudono; Rini; Sri Sudono Saliro (FAKULTAS HUKUM UM PAREPARE, 2021)
This research was motivated by the fact that many officers who served as investigators still did not hold an S1 degree or equivalent so that the provisions for investigators had not met the provisions of Government Regulation Number 58 of 2010 concerning Amendments to Government Regulation Number 27 of 1983 concerning Implementation of KUHAP Article 2A. paragraph (1) letter a concerning requirements for investigators. The type of research used is field research using Field Research, which is to find events that become the object of ongoing research, both from direct information and conditions in the field. The data collection techniques used were interviews and documentation based on primary sources in the field, and secondary sources based on books or research work related to this research. Based on the results of the research supported by several sources and theories of legal effectiveness, it was concluded that it was found that investigators did not have an S1 degree so that the Sambas Police and its staff were not yet effective in its implementation.